Subfunctionalization of a Retinoid-Binding Protein Provides Evidence for Two Parallel Visual Cycles in the Cone-Dominant Zebrafish Retina - Fleisch, Valerie C. (J Neurosci, 2008)
In vertebrates, the absorption of a photon results in an 11-cis to all-trans isomerization of the retinylidene chromophore of cone and rod visual pigments. To sustain vision, metabolic pathways (visual cycles) have evolved that recycle all-trans-retinal back to 11-cis-retinal. The canonical visual cycle takes place in photoreceptor cells and the adjacent retinal pigment epithelium (RPE). Biochemical analyses provided evidence for the existence of an additional cone-specific visual cycle involving Müller glia cells, but none of its molecular components has yet been identified. Here we took advantage of the zebrafish retina to investigate the role of the cellular retinaldehyde-binding protein CRALBP in this process. We found that the zebrafish genome encodes two cralbp paralogs: cralbp a and cralbp b. These paralogs are differentially expressed in the retina. Cralbp a is exclusively expressed in the RPE, and Cralbp b is localized to Müller cells. We used an antisense morpholino approach to knock down each cralbp paralog. Analysis of 11-cis-retinal levels revealed that visual chromophore regeneration is diminished under both conditions. Visual performance, as assessed by electroretinography, revealed reduced light sensitivity in both Cralbp a- and Cralbp b-deficient larvae, but it was more pronounced in Cralbp b-deficient larvae. Cralbp b-deficient larvae also exhibited significant deficits in their visual behavior. Together, these data demonstrate that Cralbp expression in Müller cells is essential for cone vision, thereby providing evidence that both the canonical and the alternative visual cycle depend on the same type of retinoid-binding protein.